PENGARUH PERAN SATUAN PENGAWASAN INTERNAL TERHADAP PENCAPAIAN GOOD UNIVERSITY GOVERNANCE PADA PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) DI INDONESIA - Purwanto Wahyudi; Murdifin Haming; Asriani Junaid (AkMen JURNAL ILMIAH, 2018)
This research aims to know whether the Internal Control Unit (ICU) has a role to achieve the Good University Governance (GUG) at State Islamic Universities (SIU) in Indonesia This study use primary data which collected by questionnaire share to every respondents . Population in this research are the internal auditors who work on Internal Control Unit (ICU) at the State Islamic Universities (SIU) in Indonesia . The method approach in this research is kuantitative by using simple linear regression analysis.The result shows that Internal Control Unit (ICU) significantly affect the Good University Governance (GUG) achievement at State Islamic Universities (SIU) in Indonesia. So,the conclusion is the Internal Control Unit (CIU) has a role to the Good Universitty Governance (GUG)achievement. It means that in applying of good governanceprinciples in universities, need the role of Internal Control Unit (ICU) as an independent unit to ensure non-academic quality in a university.